Nutrition intervention in scholars - Carolina Anzolin; Camila Marcon Ouriques; Doroteia Aparecida Höfelmann; Tatiana Mezadri (Universidade de Fortaleza, 2010)
Objective: To verify the effectiveness of nutrition intervention in changing dietary intake among school children aged 6 to 10 years old in private school, in the city of Itajaí - SC, Brazil. Methods: A non-randomized and uncontrolled intervention study, carried through four educational activities in the period from August to November, 2008 and food intake reassessed at the end. We evaluated the nutritional status by means of body mass index for age and sex, and waist circumference. The frequency of consumption before and after intervention was compared using the paired Student t test. Results: Joined in the survey 93 students (69.92%) of whom 48 children (54.5%) were normal weight, while 36 (40.9%) were overweight or presented obesity. The most consumed food groups, before and after intervention were: crackers and pasta; rice and fruit juice. The average frequency of sweets intake decreased after the intervention (0.54 to 0.24 times per day, p <0.001), however increased the intake of fried potatoes (0.25 to 0.65, p <0.001), pizza and hamburger (0.30 to 0.46, p = 0.028). Among girls, the intake of sweets decreased after the educational activities (0.58 to 0.12, p <0.001). Conclusions: Nutritional interventions, despite the short period of time, were effective in changing the consumption of certain foods / food groups. The results reinforce the need to carry out interventions more often and for longer periods, to promote effective changes in food consumption.